Pancasila Values and Peace Verses as Resilience Against the Religious Extremism: Study on Nahdlatul Ulama and Shi'a - Muh Khamdan; Wiharyani; Nadiah Abidin (Universitas Muhammadiyah Malang, 2024)
The article explains the contestation and commodification of ideology in changing patterns of extremist movements in society. Ideological problems are studied using a political sociology approach to describe the relationship between Pancasila values ​​and peaceful verses in Islam with the phenomenon of changing movement patterns of terrorist networks in Indonesia. This paper uses a qualitative method that explains the data descriptively so that the construction of the data is understood as the result of interpretations that have plural dimensions or depend on the analytical point of view. The primary sources for this research are documents related to the themes of Pancasila values ​​and peaceful verses in the Koran and patterns of building immunity against extremism. The data processing process based on some documents was carried out using the content analysis method using the descriptive analysis method. Ideological identity in contestation in Indonesia is only one of the differentiation strategies to win public sympathy. Identity politics, which is often associated with radicalism and fighting between religious groups, is different from what happens in politics in other countries. The phenomenon of the life of the Nahdlatul Ulama and Shi'a community in Jepara, which tends to be peaceful and quick in resolving conflicts based on religious ideology, is at least influenced by awareness of the values ​​of Pancasila as a common consensus.